Learning a tragic news: a diffusion study of the Malaysian plane shot over Ukraine - Syed Abdullah Idid, Syed Arabi (2015)
This study examined how news about the Malaysian plane that was shot down in Ukraine, was diffused nationwide. The tragic incident is regarded as one of the unexpected significant events of the year. This study investigated how Malaysians received and subsequently spread the news on the downing of the plane, resulting in the deaths of 283 passengers and 15 crew members on board. Malaysia Airlines Flight 17, a passenger flight that departed from Amsterdam to Kuala Lumpur, was alleged to have been shot down by a Buk surface-to-air missile near Torez in Donetsk Oblast, Ukraine on 17 July 2014. Earlier in the year on March 8, Malaysia Airlines Flight 370, Boeing 777 flying from Kuala Lumpur to Beijing vanished when it lost contact with the air traffic control at 2.40 am. The news of this MH17 flight quickly spread around the globe through the various media channels. Specifically, this study explored (1) the spread of news from the time news was announced, (2) compared the differences in learning about the news by gender, race and age; (3) determined the medium most preferred to by the audience in the spread of news, and (4) identified the pattern of interpersonal communication in the diffusion of news. Data, collected on 1,003 adults nationwide through the use of a questionnaire, were analyzed using Statistical Package for Social Sciences (SPSS) WIN 20. Given the differential time across the continents, the first news announcement to reach Malaysia was at 11 pm, and it was too late for the majority of Malaysians who had gone to bed to hear of the event. The timing of the event and the Malaysian media use behaviour affected the diffusion of news about the tragic event. The news about the significant event spread slowly making the event appear to have lost its significance partly due to the timing of the event and the media behaviour of Malaysians. The study also examined the role of the media in relaying news and how Malaysians relied more on the mainstream media to spread the news among friends and family members.